Design and Experiment of a Hand Movement Device Driven by Shape Memory Alloy Wires. (31st March 2021) - Wang, Yangwei; Zheng, Shufang; Pang, Jingquan; Li, Sanping; Li, Jian
Abstract : Hand is one of the most flexible and useful organs of the human body. However, cases of hand function loss due to diseases and accidents abound, which brings a lot of inconvenience to patients' lives. This paper introduced a flexible hand movement device (HMD) driven by shape memory alloy (SMA) wires, which is compact, lightweight, and easy to use during activities of daily living (ADL). Firstly, we elaborated the design and modelling process, including the driving analysis of SMA wires. Secondly, the manufacturing process and testing method of the HMD are presented. Thirdly, the results of the experiment are discussed in detail. Through the experiment, we obtained the bending angle and operating space of fingers. Moreover, the joint angle as well as the fingertip force can be controlled using PWM. A maximum angular movement of 45°, 62°, and 71° can be generated at the metacarpophalangeal (MCP), proximal interphalangeal (PIP), and distal interphalangeal joints (DIP) of a finger using an SMA wire, respectively. Then, the operating space of the entire hand can be calculated based on the experimental results. Besides, an estimated 40 N of grasping force can be produced for a whole hand. In conclusion, this research indicates that the finger movement driven by the HMD is similar to a healthy person, which can meet the needs of ADL.